Optimizing the ability of ambulance drivers in handling emergency situations in Gunungkidul Regency, Yogyakarta - Sumarti Endah Purnamaningsih Maria Margaretha; Sugiarto Sugiarto (Community Empowerment, 2022)
The ambulance driver is one of the parties that participates in helping victims. The purpose of this community service is to optimize the role of ambulance drivers in providing assistance in emergency conditions which include evacuation, stabilization, transportation. In an effort to optimize, counseling is needed related to emergencies that often occur. The implementation of this program is carried out in three stages, namely, pre-test, counseling, and post-test. This program succeeded in increasing the understanding of ambulance drivers regarding emergency conditions, both aspects of evacuation, stabilization, and transportation.